Comparison of Deterministic and Geostatistical Inversion Results from a Petroleum Field - Filardi, Márcia Cristina Lohmann; Bettini, Claudio; Schwedersky Neto, Guenther (Anuário do Instituto de Geociências, 2016)
The most effective way to integrate seismic data in the reservoir characterization process is through the generation of impedance models derived from seismic inversion. In this work we compared the deterministic and geostatistical seismic inversion results of an oil field in order to improve the characterization of the field and generate a more accurate model, where the field behavior predictions could be done in a more effective way. The deterministic acoustic inversion is a widely used technique, which yields a single result, inverting the seismic data available for acoustic parameters (P-impedance). Geostatistical acoustic inversion generates multiple models of reservoir properties (elastic, lithology and petrophysical parameters), all of them equally probable, leading to the possibility of quantifying the uncertainty surrounding the reservoir model being created.